Intravenous paracetamol vs tramadol for pain management in patients with acute pancreatitis - Shrestha, Roshan; Khanal, Ajit; Paudel, Nandu; Karki, Sanjit; Sah, Manoj (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Acute Pancreatitis causes severe and persistent pain, and thus, necessitates effective treatment. Opioids are widely used to relieve pain in acute pancreatitis due to their efficacy and effectiveness. Intravenous paracetamol has been documented to have comparable effectiveness as that of opioids, with lesser side effects. In this study, the analgesic efficacy of tramadol, an opioid was compared with paracetamol in acute pancreatitis. Method: This was an open label comparative study conducted in a tertiary referral hospital of Nepal. Patients with Acute Pancreatitis were randomly assigned to receive 1 g of paracetamol or 50 mg of tramadol with 100 mL normal saline within 4-5 minute. Pain measurements of the patients were conducted at baseline and 24 hours after the treatment intervention. Changes in pain scores were calculated by subtracting the mean scores at baseline and 24 hours as pairs. Result: In this study, 80 patients were enrolled and included in the final analysis. The study subjects had a mean age of 39.33 +/- 13.3 years and 62(77.5%) of them were male. Alcohol was the etiology for pancreatitis in 67.5% (n=54) of patients. Mean pain scores at baseline and 24 hours were similar in the two groups. Similarly, change of scores from baseline to 24 hours did not differ between the groups. Comparison of pain improvements failed to reveal any differences between groups. Conclusion: Intravenous paracetamol is an effective alternative to tramadol in pain management of acute pancreatitis.